Launching Stealth AutoGuideTM robot for stereotactic biopsy procedures in a neurosurgical centre: learning curve and workflow optimization - Barth, Marcus; Holl, Etienne; Flaschka, Fabian; Karakaya, Sila; Körbler, Vitus; Pichlsberger, Melanie; Wolfsberger, Stefan; Micko, Alexander (Frontiers in Robotics and AI, 2024)
BackgroundAccurate histological analysis is crucial for confirming intracerebral neoplasia due to the diverse array of potential diagnoses presented by imaging. In the realm of biopsy techniques, the use of robot-based systems is on the rise, primarily owing to their heightened targeting accuracy. The objective of this study was to elucidate the practicality, learning curve and workflow associated with robot-guided biopsies upon their introduction to a neurosurgical centre.Materials and methodsIn March 2022, the neurosurgical department at our institution adopted the Medtronic Stealth AutoGuide™ cranial robotic guidance platform, a miniaturized robotic guidance device designed for stereotactic procedures. Four experienced neurosurgeons underwent training with the Stealth AutoGuide™ system, after which 51 consecutive biopsies were performed. The evaluation encompassed entry and target accuracy, preoperative setup time, time required for the biopsy procedure, and overall operating time. Statistical analysis was conducted to identify any differences between the initial 26 and subsequent sets of 25 patients, with the aim of identifying changes in workflow.ResultsThe study included all patients necessitating a diagnostic biopsy for intracerebral tumours, with only one patient excluded due to the inaccessibility of the intended target point caused by tumour calcification. Notably, there were no significant differences between the first 25 and last 26 patients in the median time from incision to the first biopsy (overall: 11.5 min, IQR 9.03–15.0), the procedure time (overall: 30.0 min, IQR 23.5–46.5), median accuracy at entry (overall: 2.05 mm, IQR 0.8–3.8), or target point (overall: 2.2 mm (IQR 1.6–3.7). However, a significant reduction in robot setup time was observed between the two groups, median 2.69 min versus 1.17 min, respectively (p ≤ 0.001).ConclusionThe deployment of the robotic biopsy system, Stealth AutoGuide™, showed high feasibility, steep learning curve due to uncomplicated technical handling using our standardized operative workflow. Therefore, even in prone position a high diagnostic yield was achieved. Overall, the Stealth AutoGuide™ system facilitated biopsies in traditionally challenging regions with concise procedure time and surgeon-independent high accuracy.